2020
DOI: 10.1080/1331677x.2020.1863830
|View full text |Cite
|
Sign up to set email alerts
|

How COVID-19 has shaken the sharing economy? An analysis using Google trends data

Abstract: COVID-19 pandemic has disrupted the economies around the world and the economic fallout from preventive measures such as lockdown is enormous. It has massive repercussions for the sharing economy as well. This research paper empirically analyses the impact of lockdown restrictions on five major sectors of the sharing economy such as ride-hailing, accommodation, freelance work, entertainment and delivery services. To evaluate this impact, we employed the difference-in-difference estimation technique using the G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
73
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 89 publications
(75 citation statements)
references
References 26 publications
(23 reference statements)
1
73
0
1
Order By: Relevance
“…However, all of them analyzed the growth-inflation relation using time domain analysis. Barro (1995) analyzed the growth-inflation relationship using data for more than 100 countries over the period 1960-1990 and found a negative relationship, whereas Anidiobu et al (2018) found that the relationship between growth and inflation is positive but non-significant in the case of Nigeria using data from 1986 to 2015. Shahid (2014) studied the long-run relation between inflation, unemployment, and economic growth in the case of Pakistan.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, all of them analyzed the growth-inflation relation using time domain analysis. Barro (1995) analyzed the growth-inflation relationship using data for more than 100 countries over the period 1960-1990 and found a negative relationship, whereas Anidiobu et al (2018) found that the relationship between growth and inflation is positive but non-significant in the case of Nigeria using data from 1986 to 2015. Shahid (2014) studied the long-run relation between inflation, unemployment, and economic growth in the case of Pakistan.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Such is the importance of COVID-19 in the world that, in a short time, multiple studies have analyzed the influence of the pandemic on different aspects such as geopolitics (Heisbourg, 2020;Sharif et al, 2020), socioeconomics (Nicola et al, 2020a;van Barneveld et al, 2020), healthcare policy (Nicola et al, 2020b), the sharing economy (Batool et al, 2020), socially responsible investment or climate change policy (Cole & Dodds, 2021). Studies that analyze the impact that COVID-19 has on the solvency of companies can also be found or how COVID-19 has affected the credit portfolios of financial institutions (Yarovaya et al, 2020a).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, financial companies seem to exhibit higher increases of correlations than non-financial firms. Other perspectives can also be identified in literature, like evaluating the impact of the pandemic on other selected economic sectors (Batool et al 2021).…”
Section: Literature Reviewmentioning
confidence: 99%